Non‐syndromic bilateral ulnar aplasia with humero‐radial synostosis and oligo‐ectro‐dactyly. Issue 5 (10th February 2018) - McVeigh, Terri P.; Soye, Jonathan A.; Gordon, Emma; Lynch, Sally A.
Abstract : Congenital anomalies of the upper limbs are rare and etiologically heterogeneous. Herein, we report a male infant with non‐syndromic bilateral Type Vb ulnar longitudinal dysplasia with radiohumeral synostosis (apparent humeral bifurcation), and bilateral oligo‐ectro‐syndactyly who was born following an uncomplicated pregnancy, with no maternal use of prescription or illicit medication. Array CGH (60, 000 probes) and chromosomal breakage analysis (DEB) were normal. Similar appearances have been reported in children exposed to thalidomide or cocaine, but sporadic patients have also been reported without a prior history of exposure to known teratogens.